Isolation and characterization of opportunistic fungi causing secondary infection in debilitated patients - Rai, Sapna; Tripathi, Preeti; Saraf, Ashish (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> An opportunistic infection is caused by variety of pathogens such as bacteria, virus, fungi or protozoans that usually do not cause disease in a healthy host. In order to accomplish the objectives of the present research work clinical samples were collected from debilitated patients. Out of 45 samples 27 were found to be positive for fungal infection. A total number of 76 mold form and ample number of Candida spp. clinical isolates were obtained. The common molds isolated were Alternaria alternata, A. fumigatus, A. niger, A. terreus, A. nidulans, A. flavus, Rhizopus spp. Mucur spp. and Curvularia lunata. In order to study the antifungal profile of the clinical isolates in vitro antifungal susceptibility test was performed by Kirby Bauer Method. Ketoconazole was found to be most effective azole against the clinical isolates followed by Clotrimazole, Itraconazole and Amphoterecin B.